2008
DOI: 10.1088/0004-6256/136/1/344
|View full text |Cite
|
Sign up to set email alerts
|

VERY LARGE ARRAY AND VERY LONG BASELINE ARRAY OBSERVATIONS OF THE HIGHEST REDSHIFT RADIO-LOUD QSO J1427+3312 ATZ= 6.12

Abstract: We present 8.4 GHz VLA A-array and 1.4 GHz VLBA results on the radio continuum emission from the highest redshift radio-loud quasar known to date, the z = 6.12 QSO J1427+3312. The VLA observations show an unresolved steep spectrum source with a flux density of 250 ± 20 µJy at 8.4 GHz and a spectral index value of α 8.41.4 = −1.1. The 1.4 GHz VLBA images reveal several continuum components with a total flux density of 1.778±0.109 mJy, which is consistent with the flux density measured with the VLA at 1.4 GHz. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 29 publications
(41 reference statements)
3
50
2
Order By: Relevance
“…The quasar J1659+2101 is somewhat more resolved than the others. Notably, the two most distant (z ∼ 6) quasars (J0836+0054, Frey et al 2003Frey et al , 2005J1427+3312, Frey et al 2008bMomjian et al 2008) observed with VLBI to date share much similar properties.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The quasar J1659+2101 is somewhat more resolved than the others. Notably, the two most distant (z ∼ 6) quasars (J0836+0054, Frey et al 2003Frey et al , 2005J1427+3312, Frey et al 2008bMomjian et al 2008) observed with VLBI to date share much similar properties.…”
Section: Discussionmentioning
confidence: 91%
“…Recent surveys that did not apply spectral selection criteria (e.g. Mosoni et al 2006;Frey et al 2008a), and VLBI observations of individual z ∼ 6 quasars (J0836+0054, Frey et al 2003Frey et al , 2005J1427+3312, Frey et al 2008bMomjian et al 2008) indicate that there is a less-known steep-spectrum population of compact radio AGNs at high redshifts. These sources have so far been able to escape discovery for a variety of reasons: (i) their radio flux density is relatively low for VLBI, requiring high data rate phase-referenced observations; (ii) due to their steep spectra, they are generally not considered useful for VLBI experiments; (iii) for most of them, spectroscopic redshifts are simply not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Additionaly, recent VLBI studies suggest that the naive ⋆ E-mail: gabanyik@sgo.fomi.hu; krisztina.g@gmail.com expectation that relativistically beamed sources (blazars) should dominate the high-redshift radio-loud quasar population might not be true. There seems to exist a population of steep-spectrum high-redshift (z 4.5) radio-loud quasars (Momjian et al 2008;Frey et al 2008Frey et al , 2010, which may be very young radio quasars, similar to the gigahertzpeaked spectrum (GPS) sources observed in the local Universe (Frey et al 2010). On the other hand, a few highredshift, beamed blazars are known as well.…”
Section: Introductionmentioning
confidence: 97%
“…(The powerlaw spectral index α is defined as S ∝ ν α , where S is the flux density and ν the frequency.) The 1.4-GHz and 1.6-GHz VLBI images of the first z > 6 radio quasar, J1427+3312 (Momjian et al 2008;Frey et al 2008, respectively) revealed a prominent double structure. The two resolved components are separated by ∼28 mas (∼160 pc); to calculate linear sizes and luminosities, we assume a flat cosmological model with H 0 = 70 km s −1 Mpc −1 , Ω m = 0.3, and Ω Λ = 0.7.…”
Section: Introductionmentioning
confidence: 98%